Putting the Squeeze on 'Generation Rent': Housing Benefit Claimants in the Private Rented Sector - Transitions, Marginality and Stigmatisation. (May 2016) - Cole, Ian; Powell, Ryan; Sanderson, Elizabeth
The term 'Generation Rent' has gained currency in recent years to reflect the fact that more 25 to 34 year olds in Britain now live in rented accommodation rather than owner-occupation. The term also conveys the extent to which age-related divisions in the housing market are becoming as significant as longer standing tenure divisions. However, this portmanteau term covers a wide array of different housing circumstances - from students, young professionals and transient households to the working and non-working poor. This paper focuses on the position of a specific category of this age cohort - those 25 to 34 year olds living in self-contained accommodation in the private rented sector who are in receipt of Housing Benefit. On the basis of survey evidence and qualitative interviews with landlords and housing advisers, the paper considers how the marginal economic and housing market position of this age group is being reinforced by the stigmatising attitudes of landlords which formerly applied to tenants in their late teens and early 20s and are now being extended further along the age band. The paper suggests that the use of a 'housing pathways' approach to signify the housing transitions of young adults needs to be revisited, to give greater weight to collective and creative responses to constraints in the housing market and to recognise the key role played by gatekeepers such as landlords in stigmatising groups according to assumed age-related attributes.